Propuesta de un plan estratégico para la empresa “Mercantil Flores Campoverde Cía. Ltda.” de la ciudad de Loja - Flores Campoverde, Ximena del Cisne (2015)
The actual investigation arises as a general objective “THE PROPOSAL OF A STRATEGIC PLAN FOR “MERCANTIL FLORES CAMPOVERDE CÍA. LTDA”. ENTERPRISE” FROM LOJA CITY”, which permitted to do a proposal to a better guidance of its activities, in order to reach a position in the market and receive incomes in the enterprise. The thesis project starts with the RESUME, where a revision of each phase of the thesis is made in a general way emphasizing the obtained results along the investigation; after this there is the Introduction, where the searched problem is placed in a specific context and it is made an analysis in a general form of the present work about its most important aspects, then the Literature Review is exposed and it is based in the theory of different authors who permitted to put in practice their theories in the proposal development. Following these, there are the Materials and Methods, where the materials used to the development of the investigation are written, also the use of methods as: descriptive, analytic, inductive, and deductive; apart of that, there are applied techniques as: the interview made to the enterprise’s manager, the interview made to internal customers (employees) with a total of 13 employees and the interviews to external customers, to do that it was determined a sample of 381 customers who were used as a base to recollect information data. After this , the Results are shown where the situational diagnosis of the enterprise “MERCANTIL FLORES CAMPOVERDE CÍA. LTDA.”is made in the first instance, this diagnosis is formed by an internal auditory in its different areas marking again its strong and weak points. In second instance the external analysis is exposed, it is based on external factors that affect to the enterprise and then it is exposed an internal analysis through an interview made to the General Manager, and interviews made to internal and external customers from the enterprise. From this it was possible to determine the stub EFE whose result was 2.56, which means that the enterprise is over the average of 2.50, this shows that the enterprise takes advantage in an adequate form the opportunities about its threats, and EFI stub where the result was 2.74, it represents that the enterprise is over the average of 2.50, this means that the enterprise has more fortresses than weaknesses. With EFE and EFI stubs results it was built FODA stub as one of the specific objectives, it permitted to determine fortresses, opportunities, weaknesses and threats from the enterprise; the fortresses must be done with power and the opportunities must be taken in advantage for a better development. From FODA stub was obtained the stub of High Impact, this stub permitted to come up strategies with different strategic guidence. The proposal for strategic objectives is made in the Discussion, to perform it there were arosed different goals, strategies, tactics, and activities, there were assigned responsible people and it was determined the budget for each one of them, the budget amounts to $15,434.08 dollars. The strategic objectives which were planted were: 1. Increase the Number of Customers of the Company in the period 2015. 2. Maximize Participation Products and improve the image of the company in the market lojano. 3. Loyalty to the Future Current Customers and providing confidence and rewarding them for their loyalty 4. Improving Knowledge, Skills and Qualities Human Resource Business 5. Increase the sales of the Company in the Year 2015 6. Lay down and delimit tasks , powers and responsibilities to each Work Area Business The CONCLUSIONS are after all of these, here it is possible to highlight that through the diagnosis it was made an internal auditory in order to do an analysis of each one of the areas from the enterprise, it permitted to compare with the field investigation through the collaboration of its human talent. After this there are the RECOMMENDATIONS for the enterprise, among the most important there is the rising of strategic plan, it is proposed with the objective to improve the actual situation of the enterprise, to encourage a bigger compromise by the enterprise’s employees and in this way to obtain optimum results to have the commercial activity of the enterprise